Three-dimensional printing of blue-colored zirconia accessories using digital light processing-based stereolithography - Li, Yanhui; Wang, Shengliang; Wang, Minglang; Zhang, Xinyue; Lu, Binwen; Wang, Yueliang; Dong, Dongdong; He, Fupo; Liu, Wei; Wu, Shanghua (Journal of Asian Ceramic Societies, 2021)
Digital light processing (DLP) based stereolithography opens new possibilities for fabricating ceramic accessories with complex structures. The cure depth is a critical criterion for analyzing the production efficiency of ceramic accessories. As predicted using the absorption model, the absorbance from the photoinitiator and dye has a direct effect on the cure depth. In this study, blue-colored powder composed of 3 mol% yttria-stabilized tetragonal zirconia polycrystals (3Y-TZP) and CoAl 2 O 4 powder was prepared through ball-milling. The cure depth of a single layer exposed to varying energy levels was measured, and the values of the depth sensitivity S d and critical energy E c were also calculated. The results showed that the absorbance of blue-colored 3Y-TZP powder increased with CoAl 2 O 4 content, which increased the critical energy E c and depth sensitivity reciprocal 1/S d . Compared with the pure 3Y-TZP, the cure depth decreased, which was attributable to the absorbance of CoAl 2 O 4 . In addition, blue-colored accessories were fabricated using the DLP method, and the microstructures of the accessories were characterized through scanning electron microscopy.